Determinant Factors Of Business Resilience In Fishery Processing SMEs During The Covid 19 Pandemic - Ian Nurpatria Suryawan; Innocentius Bernarto; Ronnie Resdianto Masman (Jurnal Manajemen, 2022)
Fisheries processing entrepreneurs in Jakarta focus on developing strategic management by increasing innovation capabilities so as to improve organizational performance and have a significant competitive advantage so that they can survive the covid 19 pandemic. The population is 4 (four) DKI Jakarta municipality area with total sample of 100 fishery processing entrepreneurs. Samples were taken randomly and performed at some stage in February 2022. For records processing using convenience sampling. The study prove that competitive intensity has affect on organization performance, competitive intensity has affect on organization innovation, competitive intensity has affect on organization performance mediated by means of organization innovation, organizational slack has have an effect on on enterprise innovation, organizational slack has affect on business enterprise performance, organizational slack has affect on organisation overall performance mediated through organisation innovation, organization innovation has affect on organization performance although not sizeable.